Determination of the surface relaxivity of soft sediment using particle size and shape - Nick J. Hol; Ismail Myouri; Claire Chassagne; Leo Pel (Journal of Magnetic Resonance Open)
This study presents a method to determine surface relaxivity in soft sediments by combining one-dimensional Nuclear Magnetic Resonance (NMR) imaging with particle size and shape estimates. In order to determine the surface relaxivity up to now often methods like Mercury Intrusion Porosimetry or Brunauer–Emmett–Teller (BET) are used which where drying steps are involved which can alter material properties during analysis, particularly in highly deformable materials, making these techniques unreliable for soft soils. By combining NMR relaxometry and estimates of particle sizes and shapes of a soft soil, this new approach provides accurate, non-invasive surface relaxivity measurements. This method is demonstrated on kaolinite, glass beads, and natural soils, showing that this method supports detailed assessment of pore size distributions in soft sediments, benefiting geotechnical and environmental research where soil stability is critical.